Surgical treatment of urethral tuberculosis in men – history and present (literature review) - A. A. Volkov; O. N. Zuban; M. N. Reshetnikov; D. V. Plotkin; E. M. Bogorodskaya (Acta Biomedica Scientifica, 2021)
The literature review provides data on tuberculosis of the urethra in men. This disease is rarely recorded, as a rule, at the stage of formation of the urethral stricture, which can develop many years after the onset of the disease. Urethral tuberculosis is usually secondary to other localizations of extrapulmonary tuberculosis, such as tuberculosis of the prostate, penis, kidney, and bladder, but there are also isolated forms of this disease. The most common symptoms of urethral tuberculosis are the presence of strictures, skin-urethral and recto-prostatic fistulas, and purulent urethritis. Almost always, with this disease, conservative specific therapy was carried out, which in some cases made it possible to completely eliminate the symptoms and ensure the patient’s clinical recovery. Tuberculous urethral strictures are operated on according to generally accepted rules, but there is no single algorithm for the surgical treatment of strictures of this etiology, often limiting itself only to urine diversion or urethral dilation. Of the urethroplasty, the most commonly used end-to-end urethral anastomosis. In our opinion, a promising direction is the use of various grafts for the surgical treatment of this disease.